Espacios vitales de aprendizaje: su ecología en el sétimo año de la educación pública costarricense - Alfaro Rodríguez, Magdalena (2010)
The present article is the result of an investigation between CIDE-UNA to build a desirable profile for teachers that might teach seventh grade in Costa Rican public education schools. This article evidences transparency in the ecology of learning spaces, known as the environment, the actors involved and their complex interrelations. There is also a description of these spaces and their incidence in the permanence and promotion of the students population, in the singular moment in which the educational system imposes them the first and rough institutional changes coinciding with physical transformations and social and familiar relationships.